Is Ring Breaking Feasible in Relative Binding Free Energy Calculations? - Liu, Shuai (J Chem Inf Model, 2015)
Our interest is relative binding free energy (RBFE) calculations based on molecular simulations. These are promising tools for lead optimization in drug discovery, computing changes in binding free energy due to modifications of a lead compound. However, in the “alchemical” framework for RBFE calculations, some types of mutations have the potential to introduce error into computed binding free energies. Here, we explore the magnitude of this error in several different model binding calculations. We find that some of the calculations which involving ring breaking have significant errors, and this error is especially large in bridged ring systems. Since the error is a function of ligand strain, which is unpredictable in advance, we believe ring breaking should be avoided when possible.